2014
DOI: 10.1371/journal.pone.0099915
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intestinal Fatty Acid-Binding Protein in Predicting Strangulated Small Bowel Obstruction

Abstract: BackgroundThe level of intestinal fatty acid-binding protein (I-FABP) is considered to be useful diagnostic markers of small bowel ischemia. The purpose of this retrospective study was to investigate whether the serum I-FABP level is a predictive marker of strangulation in patients with small bowel obstruction (SBO).MethodsA total of 37 patients diagnosed with SBO were included in this study. The serum I-FABP levels were retrospectively compared between the patients with strangulation and those with simple obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
3
28
1
1
Order By: Relevance
“…The concentration of CRP, a plasma protein, rises dramatically as a result of cytokine-mediated responses to most forms of infection, inflammation, and tissue injury. [27] In this study, serum CRP was not significantly different between the NSG and SG, as was found in the study of Kittaka et al [9] Also, Simon et al reported that, for bacterial infections, serum CRP has little sensitivity and specificity. [28] We feel that further study is needed to determine the usefulness of CRP in this regard.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The concentration of CRP, a plasma protein, rises dramatically as a result of cytokine-mediated responses to most forms of infection, inflammation, and tissue injury. [27] In this study, serum CRP was not significantly different between the NSG and SG, as was found in the study of Kittaka et al [9] Also, Simon et al reported that, for bacterial infections, serum CRP has little sensitivity and specificity. [28] We feel that further study is needed to determine the usefulness of CRP in this regard.…”
Section: Discussionsupporting
confidence: 76%
“…However, other reports found no difference in terms of time of symptom onset to ED arrival between SG and NSG. [8,9] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a retrospective study 34 has shown that increase in I-FABP levels in patients with small bowel obstruction can be used to predict strangulation. The I-FABP can be increased with dynamic recycling of enterocytes during ischemia or strangulation, but I-FABP measurement requires a long period of time, while measurement of serum CRP and serum D-lactate can be done in a short span of time.…”
Section: Discussionmentioning
confidence: 99%
“…Kittaka et al [53] found that serum I-FABP concentrations were significantly increased in patients with strangulated bowel obstruction (n = 21; 18.5 ng/mL), as compared with patients with simple obstruction (n = 16; 1.6 ng/mL).…”
Section: Fatty Acid-binding Proteins (Fabp) Biomarkers Of Villi Injurymentioning
confidence: 98%